The manufacturing sector of the city of Cúcuta facing the socioeconomic crisis with Venezuela (2020)
The objective of the article is to analyze the manufacturing sector of the city of Cúcuta in the face of the socioeconomic crisis in Venezuela and the border context. The research is part of the empirical-analytical paradigm and corresponds to a descriptive, non-experimental, transectional quantitative study. A validated questionnaire was used, which was applied to 130 companies. Four variables were analyzed: managerial profile, general characteristics, operating environment and financial management.